2017
DOI: 10.1111/bph.13973
|View full text |Cite
|
Sign up to set email alerts
|

Antidote to cannabinoid intoxication: the CB1 receptor inverse agonist, AM251, reverses hypothermic effects of the CB1 receptor agonist, CB‐13, in mice

Abstract: BACKGROUND AND PURPOSECannabis is a recreational drug leading to intoxication, following stimulation of cannabinoid CB 1 receptors. However, more recently, herbs mixed with synthetic cannabinoids sometimes known as 'Spice' and 'Black Mamba' have been increasingly used, and their high CB 1 receptor affinity has led not only to marked intoxication but also life-threatening complications and an increasing number of deaths. Although many studies have indicated that prophylactic treatment with CB 1 receptor antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…CB-1 antagonists have also been shown to reverse the pharmacological effects of cannabinoids. For example, the CB-1 antagonist AM-251 has been reported to reverse the hypothermia induced by the SC, CB13 (Pryce and Baker 2017). In this study (Fig.…”
Section: Can Cb-1 Antagonists Be Used To Treat Aco?supporting
confidence: 53%
See 1 more Smart Citation
“…CB-1 antagonists have also been shown to reverse the pharmacological effects of cannabinoids. For example, the CB-1 antagonist AM-251 has been reported to reverse the hypothermia induced by the SC, CB13 (Pryce and Baker 2017). In this study (Fig.…”
Section: Can Cb-1 Antagonists Be Used To Treat Aco?supporting
confidence: 53%
“…Converging lines of evidence, including compelling clinical data, have shown that cannabinoid (CB-1) receptors mediate the principal psychopharmacological actions of both Δ 9 -tetrahydrocannabinol (THC) (the main psychoactive component in cannabis) and synthetic cannabinoids (SCs) that are likely to precipitate an ED visit (Huestis, et al 2001;Baskfield et al 2004;Zimmer et al 1999;Sain et al 2009;Pryce and Baker 2017;Marshell et al 2014;Zuurman et al 2010;Klumpers et al 2012). The identification of CB-1 receptors in 1990 (Matsuda et al 1990) and an emerging literature describing the role of endocannabinoids (e.g., anandamide) in multiple physiological processes (reviewed in Howlett et al 2002;Pertwee et al 2010) led to the development of selective, high affinity CB-1 receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of the 312 CB 1 receptor ligands, and of the 187 CB 2 receptor ligands were selected from the literature that reports the experimental K i values, primarily involving assays where isolated CB 1 and/or CB 2 receptors were incubated with a predetermined fixed concentration of radiolabeled cannabinoid ([ 3 H] CP 55,490) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 56 , 57 ]. The binding affinity data of the selected dataset were converted into their negative decimal logarithm p K i (p K i = −log K i ).…”
Section: Methodsmentioning
confidence: 99%
“…The models were created using a set of 312 CB 1 receptor ligands, and 187 CB 2 receptor ligands. Details of all the compounds having experimentally determined K i values were retrieved from the literature (i.e., anandamide analogues, benzoyl/alkoyl-indoles, cyclohexylphenols, dibenzopyrans, indazole derivatives, indazole-carboxylates, indazole-carboxamides, indole-carboxylates, indole-carboxamides, naphthoyl-benzimidazoles, naphthoyl-indazoles, naphthoyl-indoles, naphthoyl-naphthalenes, naphthoyl-pyrroles and phenylacetyl-indoles) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Figure 1 details the structures of some example of CB 1 and CB 2 ligands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increasing evidence suggests that CB 1 antagonists can reverse cannabinoid intoxication. 3 If and when CB 1 antagonists are approved for this indication, RIDR could record the clinical circumstances in which they are used and the outcomes.…”
Section: The Psychoactive Substances Act In Actionmentioning
confidence: 99%